The Influence of Giving Fe Tablets along with Guava Juice on The Increasing of Hb Levels in Pregnant Women in South Tangerang Region Health Center - Siti Rahmadani; Nurhayati Nurhayati; Erlin Puspita; Hesti Wulandari (Humanistic Network for Science and Technology (HNST), 2020)
Giving iron tablets (Fe) is one of the efforts to prevent anemia. Guava is a fruit that rich in vitamin C that can increase the absorption of Fe in the body. The purpose of this study is to analyze the influence of giving Fe tablets along with guava juice on the increasing of Hb levels in pregnant women in South Tangerang Region Health Center. This study used quasi experimental two group pre-post design. The sample consisted of 30 third trimester pregnant women with anemia which were divided into two treatment and control groups. The sampling technique used purposive sampling. Data analysis using Independent T-test, correlation and linear regression analysis. The results showed there was a significant difference between the increase in Hb levels resulting from the giving of Fe tablets along with guava juice compared with only the giving of Fe tablets with a p-value of 0.000. Multivariate analysis between treatment and control groups obtained p-value = 0.00, with the coefficient of determination (R square) = 0.748. The conclusion is giving Fe tablets along with guava juice has influence on the increasing of Hb levels in pregnant women, so it is recommended for anemic pregnant women to take Fe tablets along with guava juice Keywords: haemoglobin; anemia, Fe tablets; guava juice